Construction and topological analysis of an endometriosis-related exosomal circRNA-miRNA-mRNA regulatory network - Wu, Jingni (Aging (Albany NY), 2021)
Novel biomarkers are needed to accelerate the diagnosis and treatment of endometriosis. We performed RNA sequencing to explore the expression profiles of exosomal circular RNAs (circRNAs), microRNAs (miRNAs) and mRNAs in patients with ovarian endometriomas, eutopic endometria and normal endometria. Differentially expressed genes between the different pairs of groups were analyzed and functionally annotated. Then, miRNA-target RNA pairs were identified, competing endogenous RNA (ceRNA) scores were calculated, gene expression characteristics were determined, and these parameters were used to construct an exosomal ceRNA network. We identified 36 candidate hub genes with high degrees of gene connectivity. We also topologically analyzed the ceRNA network to obtain a hub ceRNA network of circRNAs with the highest closeness and ceRNA efficiency. Twelve genes overlapped between the 36 candidate hub genes and the genes in the hub ceRNA network. These 12 genes were considered to be exosomal RNA-based biomarkers, and circ_0026129/miRNA-15a-5p/ATPase H+ transporting V1 subunit A (ATP6V1A) were at the center of the ceRNA network. By determining the exosomal RNA expression profiles of endometriosis patients and constructing a circRNA-associated ceRNA network, these findings provide insight into the molecular pathways of endometriosis and new resources for its diagnosis and treatment.